(untitled) (Castilla. Estudios de Literatura, 2022)
Reseña sobre el libro The Voice of the Text and its Body. The Continuous Reform of Euphrase Kezilahabi’s Poetics» (Köln, Rüdiger Köppe Verlag, 2019), de Roberto Gaudioso.